A PCBM Electron Transport Layer Containing Small Amounts of Dual Polymer Additives that Enables Enhanced Perovskite Solar Cell Performance. Issue 9 (10th December 2015) - Zhu, Zonglong; Xue, Qifan; He, Hexiang; Jiang, Kui; Hu, Zhicheng; Bai, Yang; Zhang, Teng; Xiao, Shuang; Gundogdu, Kenan; Gautam, Bhoj Raj; Ade, Harald; Huang, Fei; et al.
Abstract : A polymer/PCBM hybrid electron transport layer is reported that enables high‐performance perovskite solar cells with a high power conversion efficiency of 16.2% and with negligible hysteresis. Unlike previous approaches of reducing hysteresis by thermal annealing or fullerene passivation, the success of our approach can be mainly attributed to the doping of the PCBM layer using an insulating polymer (polystyrene) and an amine‐containing polymeric semiconductor named PFNOX.